Nôtre Potager: a typology of edible landscapes in Manhattan, Kansas - Merrill, Jeremy (Kansas State University, 2009)
People living in urban and suburban areas are disconnected from agriculture. The food that we consume is grown many miles from our homes and we have little knowledge of how that food travels from seed to plate. Incorporating edible landscapes into public land in cities brings people in direct contact with the food they eat. Edible landscapes are neighborhood scale sites with the specific purpose of producing food. Edible landscapes became popular in the late 1970s. Typically developed with a focus on food production and little attention to aesthetics, the general public often thinks of these landscapes as messy and farm-like. Through quality design edible landscapes can be productive and aesthetically pleasing. The combination of these ideals create exciting and unique solutions that differ from the edible landscapes of the past. Attention to site and community design principles as well as growing conditions results in a new type of public landscape that can enhance a community’s appearance while feeding its residents. A typology of edible landscapes was applied to Manhattan, Kansas to test the potential for a community-wide system of edible landscapes. The typology is based on: garden purpose, physical characteristics, visual characteristics, and potential user groups. The inventory of public land is based upon the Diggable City project in Portland, Oregon. Potential sites were evaluated on their physical characteristics, visual profile, and design potential to determine what garden type would be most appropriate. Further analysis of each site’s design potential resulted in the selection of three sites for prototypical design development. The prototypical designs provide examples of how design principles and growing conditions can work together to create new edible landscapes and enrich the community.
Keywords: edible; typology; landscapes; Manhattan; Landscape Architecture (0390)